“In a moment of supreme discomfort.” - Perissinotto, Matteo (Prispevki za novejšo zgodovino, 2024)
The goal of this essay is to investigate from a gender perspective, through articles in the local press, the phenomenon of female suicides in Trieste during the transitional phase following WWI (1918-1922). This was due to a period of abrupt changes: political, administrative, and economic. In addition, hope for a better future and anxiety had been dashed with the increase in poverty and the rampant violence that swept through the city. In Triste in 1920 for the first time the number of female suicides exceeded the number of male suicides. Based on the judgments made in the press, three macro categories have been identified into which we can place the suicides: the “comprese” (understood) that committed or attempted suicides were considered to be socially acceptable, or at least justified, in so far as that they related to economic reasons, health or familial grief; those considered to be linked to “frivolous motives” and condemned by bourgeois morality because they were connected to matters of romance and family conflict; and finally, those of sex workers (prostitute), about whom open criticisms were put forward, as they were seen as a natural and physiological consequence of life in the brothels.
Keywords: 1918–1922; gender; Julian March; Julijska Krajina; samomori; suicide; transition; tranzicija; Trieste; Trst; zgodovina; ženske